Production of tubers from buds present in potato peel with fertilization of Trichoderma sp. - INQUILLA MAMANI, JUAN (2022)
Potato consumption occurs throughout the Altiplano of Puno and among the organic wastes produced daily at home is potato peelings. The objective of this research is the production of tubers from buds present in potato peels with four strains of Trichoderma sp. The study was carried out under an experimental design with four strains of Trichoderma sp, in a randomized way with a total of 5 treatments that were distributed with two repetitions with a total of 12 experimental units, the potato peels with buds were selected, including a fertilization with four native and commercial strains of Trichoderma, some of them were codified since the species has not yet been identified, to support the growth of seedlings so, in this way, it gives value to the "organic production". The results found evidenced that the greater quantity of tubers was obtained with the strain of Trichoderma sp. 3 with 121.50 tubers/2.4m2 (10.13 tubers/plant). Followed by the strain of Trichoderma sp. 5 with 107.50 tubers/2.4m2 (8.96 tubers/plant), which statistically were similar and superior to the other treatments, while the control had less quantity of tubers with 18.50 tubers/2.4m2 (1.54 tubers/plant). Therefore, in the millenary practice of Andean wisdom, we rescued the use of native strains of Trichoderma sp. in order to contribute to the solution of human-environmental problems and the sustainable use of potato peelings in the region.